2022
DOI: 10.46328/ijres.2747
|View full text |Cite
|
Sign up to set email alerts
|

STEAMTEACH Austria: Towards a STEAM Professional Development Program

Abstract: The STEAMTEACH (STEAM Education for Teaching Professionalism) project works with teacher trainers to develop a program of Transcultural STEAM Professional Development for in- and pre-service teachers. Following a literature review, a semi-structured questionnaire then interviews approach was used to elicit current practice, challenges for teachers and recommendations from Austrian teacher trainers. These recommendations were then compared with and supported by STEAM academic literature. It was found that none … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Professional development programs designed to guide teachers through K-12 STEAM instruction may positively impact teacher confidence in and perceptions of STEAM [16,17]. To be most effective, STEAM professional development programs are typically designed to include collaborative experiences, focused on different pedagogical methods, such as project-based learning or evidence-based learning [17,18]. Houghton and colleagues [18] describe the need for professional development settings to provide teachers with ongoing support, the relevance of STEAM in their classroom, and the ability to work collaboratively in multidisciplinary settings.…”
Section: Collaboration With Community Partners For K-12 Steam Teacher...mentioning
confidence: 99%
See 1 more Smart Citation
“…Professional development programs designed to guide teachers through K-12 STEAM instruction may positively impact teacher confidence in and perceptions of STEAM [16,17]. To be most effective, STEAM professional development programs are typically designed to include collaborative experiences, focused on different pedagogical methods, such as project-based learning or evidence-based learning [17,18]. Houghton and colleagues [18] describe the need for professional development settings to provide teachers with ongoing support, the relevance of STEAM in their classroom, and the ability to work collaboratively in multidisciplinary settings.…”
Section: Collaboration With Community Partners For K-12 Steam Teacher...mentioning
confidence: 99%
“…To be most effective, STEAM professional development programs are typically designed to include collaborative experiences, focused on different pedagogical methods, such as project-based learning or evidence-based learning [17,18]. Houghton and colleagues [18] describe the need for professional development settings to provide teachers with ongoing support, the relevance of STEAM in their classroom, and the ability to work collaboratively in multidisciplinary settings. To further enhance STEAM professional development, studies have suggested the use of community partnerships to provide teachers with new ideas for STEAM lessons and to otherwise expand knowledge on STEAM implementation [6].…”
Section: Collaboration With Community Partners For K-12 Steam Teacher...mentioning
confidence: 99%
“…Furthermore, STEAM-based hybrid based learning is one of the learning models that effectively improves students' higher order thinking skills (Rahardjanto et al, 2019;Masalimova et al, 2021;Sigit et al,, 2022). STEAM is a learning approach that combines Science Technology Engineering Arts and Mathematics in learning activities (Özer & Demirbatır, 2023;Ichsan et al, 2023;Konkuş & Topsakal, 2022;Houghton et al, 2022). This STEAM approach encourages students to be more creative and independent in learning so as to train their critical thinking skills (Frediana et al, 2021;Cobos et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, STEAM education provides an environment for students to turn their projects into products on the axis of art, design and creativity. The most important difference of STEAM education is that it makes art and design an integral part of the education model (Erdoğan, 2020;Houghton et al, 2022). STEAM education has a framework for lesson plans that show how standards can be adapted, compared, and easily reinforced in unique and engaging ways.…”
Section: Introductionmentioning
confidence: 99%
“…It is a lifelong career and a way of being ready for life that can adapt to the rapidly changing global world we live in. Moving to the STEAM perspective means learning in an educational context; it not only has a framework that shows where topics overlap, but also provides a vibrant and adaptive learning framework for ever-changing personal and unpredictable global development (Houghton et al, 2022;Morales et al, 2021).…”
Section: Introductionmentioning
confidence: 99%